Cross-sectional Study of Food Intake and Dietary Habits in Patients with Adult Periodontitis - Shimojima, Takahiro; Ikeda, Katsumi; Hiroi, Miki; Tanbo, Yumie; Sudo, Yotaro (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1997)
This study examined the intake frequency of foodstuffs and dietary habits in patients with mod-erate adult periodontitis. Forty-four patients, 26 females and 18 males, constituted the study popula-tion. The intake frequencies of various foods were investigated using a specially structured question-naire, and we required the balance-score (BS), which classifies the 12 food-types into the 6 types recognized by the Ministry of Health and Welfare, to obtain total evaluation, and to provide a score that reflected the balance of food intake. More-over, in order to investigate the relationship between BS and dietary habits (15 questions) and/or life style (8 questions), we evaluated the BS as good balance (26≥BS≥14) and as imbalance (13≥BS≥0), and we employed the chi-square test for statistical analysis. The average BS was 12.5 (female 13.1 and male 10.6), and 50.0% of females and 83.3% of males were evaluated as imbalanced. We found a rela-tionship between BS and the intake frequencies of seafood, beans, vegetables, and fruit. This means, in the imbalance group, the frequency of these foodstuffs is less, and this difference is statistically significant (P<0.01). Futhermore, we found a relationship between BS and dietary habits such as missing meals, combination of foods and preference for taste. The BS was increased in subjects who took breakfast everyday and who showed thought-ful food combination, while the BS tends was lower in the subjects with a preference for strong taste (P<0.01). In life style scores, smokers had lowes scores than non-smokers (P<0.01). These results suggest that many patients with adult periodontitis have an imbalance in food intake and this imbalance may be related to their dietary habits and life style.